Short-term climate variability in the North Atlantic during the onset of northern hemisphere glaciation and the final closure of the Panamanian seaways, 3.3 - 2.5 Ma. - Bartoli, Gretta (2005)
Long- and short-term Late Pliocene climate variations were studied at North Atlantic Sites (S.) ODP 984 and DSDP 609, supplemented by published records from S. 907 and S. 610. Foraminiferal ?18O records provided the base for stable-isotope stratigraphy. Deepwater and sea surface temperatures (SST) were reconstructed from Mg/Ca values of benthic and planktic foraminifera. Epibenthic ?___ variations were used as tracers of deepwater ventilation. Counts of ice rafted detritus served to trace back the initiation of the Greenland ice-sheet. In addition, counts of benthic foraminifera (M. Weinelt) served as tracer for primary production. Chapter 1 shows that the onset of northern hemisphere glaciation (NHG), in particular on Greenland occurred only slighty after, hence as a result of the final closure of the Central American Seaways, which led to an increase in Caribbean sea surface salinity by up to 0.9‰. A first step occurred 2.95-2.82 Ma (marine istotope stage – MIS – G16-11), a second step 2.75-2.73 Ma (MIS G6), in total amounting to ~90 m of glacial sea-level fall. The first step was coeval with an intensified Atlantic thermohaline circulation (0.2-0.3‰ increase in benthic ?13C; 2-3°C increase in SST), leading to enhanced snow precipitation in northern high-latitudes. Chapter 2 documents millennial-scale climate variations prior and after the onset of NHG at Site 984 to test the hypothesis that Dansgaard-Oeschger (DO) cycles of 1470 yr (and their multiples) are linked to ice-breakouts and meltwater incursions from northern hemisphere ice-sheets. On the long term, periodicities of 1300, 950, and 450 yr prevail, which closely resemble solar cycles of the Holocene. The same applies to selected glacial stages prior to the onset of NHG and to interglacial stages in general. However, glacial stages after the onset of NHG (MIS G14, G6, and 104) show periodicities near 1.47, 2.9 and 4.4 kyr, DO-like periodicities which thus occur in the presence of large northern hemisphere ice-sheets only, and as result of ice ...